Dermocosmetics for dry skin: A new role for botanical extracts - Casetti, F.; Wölfle, U.; Gehring, W.; Schempp, C.M.
Dry skin is associated with a disturbed skin barrier and reduced formation of epidermal proteins and lipids. During recent years, skin-barrier-reinforcing properties of some botanical compounds have been described. Searching the PubMed database revealed 9 botanical extracts that specifically improve skin barrier and/or promote keratinocyte differentiation in vivo after topical application. The topical application of Aloe vera (leaf gel), Betula alba (birch bark extract), Helianthus annuus (sunflower oleodistillate), Hypericum perforatum (St. John's wort extract), Lithospermum erythrorhizon (root extract), Piptadenia colubrina (angico-branco extract)and Simarouba amara (bitter wood extract)increased skin hydration, reduced the transepidermal water loss, or promoted keratinocyte differentiation in humans in vivo. The topical application of Rubia cordifolia root extract and rose oil obtained from Rosa spp. flowers stimulated keratinocyte differentiation in mouse models. The underlying mechanisms of these effects are discussed. It is concluded that some botanical compounds display skin-barrier-reinforcing properties that may be used in dermocosmetics for dry skin. However, more investigations on the mode of action and more vehicle-controlled studies are required.
Keywords: FILAGGRIN; KERATINOCYTE DIFFERENTIATION; SKIN HYDRATION; TRANSEPIDERMAL WATER LOSS